Innate Immunity Acts as the Major Regulator in Talaromyces marneffei Coinfected AIDS Patients: Cytokine Profile Surveillance During Initial 6-Month Antifungal Therapy. (26th April 2019) - Dong, Rong-Jing; Zhang, Yun-Gui; Zhu, Lei; Liu, Heng-Li; Liu, Jun; Kuang, Yi-Qun; Wang, Rui-Rui; Li, Yu-Ye
Abstract: Background: Talaromycosis caused by Talaromyces marneffei infection is a fatal systemic mycosis in immunosuppressed individuals, such as patients with AIDS. Cytokines and immunocytes play a central role against fungus infection. However, how the host immune system responds to infection and treatment has not been reported to date. Methods: Forty-one Talaromyces marneffei coinfected AIDS patients were followed up, their immunocytes and cytokine profiles were obtained at different antifungal treatment stages, and data on clinical features and laboratory examinations were collected. Correlation analysis was used to identify factors associated with host immunity against Talaromyces marneffei infection in AIDS patients. Results: Common diseases and conditions of these 41 patients were lymphadenopathy, hepatomegaly, and splenomegaly. CD4 + T cells were extremely low in all of them. Moreover, significant increases of proinflammatory cytokines (IL-12, IL-17A, TNF-α, IFN-γ, IL-18, and IL-1β), anti-inflammatory cytokines (IL-10), and chemokines (IP-10) were observed in talaromycosis before treatment ( P < .05), comparing to both AIDS patients and healthy controls. The cytokines IL-6, IL-8, TNF-α, IL-18, IL-17A, IL-7, IP-10, and IL-1β reached peak levels 3 days after initial antifungal therapy, and then gradually decreased. The symptoms of the patients gradually decreased. Furthermore, patients who died showed the highest levels of IL-6, TNF-α, IL-8, IL-1β, and IP-10, which were 1.4- to 164-fold higher than in surviving patients. Conclusions: Our findings indicate that innate immune-cell-derived cytokines are critical for host defense against AIDS-associated Talaromyces marneffei infection; furthermore, excessive inflammatory cytokines are associated with poor outcomes.